Indices of oxidative stress state in employees working at modern production of sulfate cellulose - N. M. Meshchakova; V. S. Rukavishnikov (Acta Biomedica Scientifica, 2013)
The products of free radical oxidation are known to exert the harmful effect on the cellular membranes which, in turn, may promote the development of the pathological processes at the level of the whole organism. The excessive process activation of the lipid peroxidation (LPO) may occur under the influence of many factors including the chemical ones, thereto, it is supposed that the LPO products may promote the toxic effects of different chemical compounds which may enter the organism from outside. The studies of the LPO state in the employees of Pulp and Paper productions were not performed. This study aimed to investigate the change features of LPO and the indices of the antioxidant defense in the employees of the main occupations at the production of sulfate cellulose exposed mainly to the methylsulfuric compounds (MSC). The study objects were the employees of main occupations of the sulfate cellulose production in Eastern Siberia. The system state of lipid peroxidation (LPO) was assessed using the determination of the primary, intermediate and final LPO products in blood plasma. The activity of the antiperoxide ferment of glutathione reductase (GR) as well as the content of SH - glutathione in the blood and the common SH - groups of the whole blood were determined to assess the state of the antioxidant defense. Statistical processing the data was performed using the computer software STATISTICA v. 6 for WINDOWS by means of the average value calculation, the standard errors of the average values, the significance assessment of the differences was performed using the STUDENTs Criterium. The significant accumulation of the primary, intermediate and final LPO products in the blood plasma was found to occur in the employees exposed to the chemical factor. Thereto, the significant decrease in the activity of glutathione reductase antiperoxide ferment of thiol disulfide metabolism as well as of SH - glutathione and the significant content decrease in the common SH-groups in blood were revealed in the employees of the boiling shifts exposed to MSC compared to the control and comparison groups. The significant statistical content dependence of the intermediate and final LPO products in the blood as well as the antioxidants on the long- term exposure to the chemical factor has been revealed. The more significant products accumulation of LPO and the index decrease in the antioxidant defense was observed to be in the employees with working period more than 10 years exposed mainly to MSC.